Pemanfaatan Digital Marketing Pada Usaha Mikto Kecil dan Menengah (UMKM) di Kota Tangerang Selatan - Siti Rozinah; Andri Meiriki (Universitas Mercu Buana, 2020)
Micro, Small and Medium Enterprises (UMKM) have an important role in the pace of Indonesia's economy, especially in job creation and household empowerment that supports household income. The existence of UMKM is expected to be able to spur the economy amid the current economic slowdown. Utilization of the concept of marketing based on digital technology (digital marketing) provides hope for UMKM to develop into a center of economic strength. The development of digital technology enables UMKM to market their products online and conduct transactions through the online banking system as well. This study aims to see whether the implementation of digital marketing can have an influence on the sales volume of UMKM industry results, as well as to find out whether the use of digital marketing has a large influence on the development of UMKM businesses in South Tangerang City. This research was conducted with a qualitative research method to look deeper into the influence of the use of digital marketing in the development of UMKM businesses in the eyes of UMKM managers in South Tangerang City. The results showed that the use of digital marketing can increase UMKM sales by 30-50 percent, and digital marketing is able to expand their market share and at the same time reduce the promotional costs they incur, as well as being able to shorten the distance of UMKM interaction with their consumers